The Pemanfaatan Jahe Merah Untuk Pencegahan dan Penatalaksanaan Kolesterol Tinggi dan Asam Urat di Dusun Kauman, Desa Gilangharjo, Kecamatan Pandak, Kabupaten Bantul: Utilization of Red Ginger for the Prevention and Management of High Cholesterol and Uric Acid Levels in Kauman Hamlet, Gilangharjo Village, Pandak District, Bantul Regency - Woro Supadmi; Muhammad Ridwan; Arini Salsabila; Ananda Ayu Chandra; Ilham Sasena (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Pekajangan Pekalongan, 2026)
High cholesterol and gout are prevalent health problems in the community and may lead to serious complications if not properly managed. This community engagement program aimed to enhance public knowledge and understanding of the use of red ginger (Zingiber officinale var. rubrum) as a supportive approach for the prevention and management of cholesterol and gout. The program was conducted in Kauman Hamlet, Gilangharjo Village, Pandak Subdistrict, Bantul Regency, employing health education sessions, dissemination of educational materials, and practical demonstrations of red ginger processing, with evaluation based on a pre-test and post-test design involving 38 participants. The results demonstrated a substantial improvement in participants’ knowledge, as indicated by an increase in the mean percentage of correct responses from 66.4% prior to the intervention to 90.5% following the intervention. These findings suggest that community-based education integrating local resources is effective in improving public understanding of cholesterol and gout prevention and management and in promoting healthy lifestyle practices.